Islamic Economics Socialization for High School Students as an Implementation of Cooperation Between Educational Institutions - Wijiharta, Wijiharta; Basyariah, Nuhbatul; Khairawati, Salihah (PT. Riset Press International, 2026)
Inter-institutional collaboration is an important strategy in strengthening the implementation of the Tri Dharma of higher education, particularly community service. This article describes a community service activity in the form of Islamic economics outreach for students of SMA Islam Terpadu (SMAIT) Insantama Bogor as an implementation of sustainable cooperation with Sekolah Tinggi Ekonomi Islam (STEI) Hamfara Yogyakarta. The activity was integrated into the Pre–Final Leadership and Management Training (Pra-LKMA) program conducted from 24 to 26 May 2025 and involved 117 students. The program employed presentation and interactive discussion methods. The materials included an introduction to STEI Hamfara’s integrated education system and the socialization of Islamic Economics from the Hamfara School of Thought using the 5i pedagogical approach. The results indicate positive participant responses and intensive interactions between students and university students, which enriched participants’ understanding of Islamic economics and pesantren-based academic culture. This activity strengthened institutional partnerships and enhanced students’ readiness for higher education grounded in Islamic values.